CORRELATION BETWEEN BIOMASS CONCENTRATION AND EXTENT OF SULPHATE REDUCTION IN AN ACIDOGENIC REACTOR - Haris, A.; Pullammanappallil, P. C.; Keller, J. (Center for Environmental Technology, 2010)
Two stage high rate anaerobic treatment systems comprising of an acidogenic reactor (or equalisation/ buffer tank) followed by a methanogenic reactor are becoming increasingly popular to treat high strength wastewater from industries.Ã‚Â In these systems, sulphate present in the wastewater is reduced to sulphide either partially or completely in the acidogenic reactor and completely in the methanogenic reactor.Ã‚Â The effect of fermentation products on the extent of sulphate reduction in the acidogenic reactor was investigated in a continuously-fed, well mixed laboratory-scale 3 L fermenter operating at a temperature of 35oC and pH of 6.Ã‚Â The feed was based on either glucose or molasses as the carbon source.Ã‚Â It was observed that as the carbohydrate concentration in feed was increased sulphate reduction was suppressed.Ã‚Â It was confirmed that volatile organic acids like acetic, propionic and butyric acids, hydrogen and residual glucose did not cause inhibition of sulphate reduction.Ã‚Â However, biomass concentration correlated negatively with extent of sulphate reduction.Ã‚Â This correlation was expressed mathematically and the same expression with the same parameters adequately predicted the effect of biomass concentration on extent of sulphate removal for both steady state and transient data irrespective of glucose or molasses feed.Ã‚Â It was seen from the best fit of this expression that a biomass concentration of 3300 mg-COD.L-1 would completely repress sulphate reduction in the acidogenic reactor.Ã‚Â Even when sulphate removal was suppressed the presence of sulphate reducing bacteria (SRB) in the reactor was confirmed through Fluorescent In Situ Hybridisation (FISH) visualisation.Ã‚Â Moreover, the numbers of SRB seemed to increase with carbohydrate concentration in feed.Ã‚Â It was speculated the suppression of sulphate removal might be due to a switch in function of SRB from sulphate reducing to fermentation or acetogenesis.Ã‚Â Ã‚Â Ã‚Â Keywords: sulphate reducing bacteria, anaerobic digestion, inhibition, sulphate reduction, acidogenic reactor, high rate anaerobic treatment